Respuesta :
assumin ya meant
[tex]f(x)=\frac{x-4}{x^2+13x+36}[/tex]
to solve, fimplify then set the denomenator equal to 0
[tex]f(x)=\frac{x-4}{x^2+13x+36}=\frac{x-4}{(x+4)(x+9)}[/tex]
hum, no simplificatoin today
so set denom equal to 0
(x+4)(x+9)=0
x+4=0
x=-4
x+9=0
x=-9
so vertical assemtotes at x=-9 and x=-4
[tex]f(x)=\frac{x-4}{x^2+13x+36}[/tex]
to solve, fimplify then set the denomenator equal to 0
[tex]f(x)=\frac{x-4}{x^2+13x+36}=\frac{x-4}{(x+4)(x+9)}[/tex]
hum, no simplificatoin today
so set denom equal to 0
(x+4)(x+9)=0
x+4=0
x=-4
x+9=0
x=-9
so vertical assemtotes at x=-9 and x=-4
Answer:
Vertical asymptote at [tex]x= -9 \ and \ x=-4[/tex]
Step-by-step explanation:
Identify the vertical asymptotes of [tex]\frac{x-4}{x^2+13x+36}[/tex]
To find vertical asymptote we set the denominator =0 and solve for x
Set [tex]x^2+13x+36=0[/tex] and solve for x
now we factor x^2 +13x+36
Product is 36 and sum is 13
[tex]9 \cdot 4=36[/tex]
[tex]9+4=13[/tex]
so the equation becomes
[tex](x+9)(x+4)=0[/tex]
Now set each factor=0 and solve for x
[tex]x+9=0, x=-9[/tex]
[tex]x+4=0, x=-4[/tex]
Vertical asymptote at [tex]x= -9 \ and \ x=-4[/tex]